2021
DOI: 10.1007/s12144-021-01743-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 continuous traumatic stressors on mental health and cognitive functioning: A case example from Turkey

Abstract: There is a need to accurately assess the specific impacts of the various traumatic stressors caused by COVID-19 on mental health. The goal was to evaluate the impact of different types of COVID-19 stressors (infection fears, lockdown, and economic stressors) on mental health and cognitive functioning. We used a sample of 262 Turkish adults. We administered an online questionnaire that included measures of COVID-19 traumatic stressors, PTSD, depression, anxiety, executive function deficits, and cumulative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 87 publications
(93 reference statements)
7
32
0
Order By: Relevance
“…Snowball sampling, in which research subjects recruit other subjects, was the most frequently used method to enroll general population study participants. The proportion of women in such samples ranged from 24.9% in Turkey 28 to 91.4% in China, 74 with nearly half of the study samples reporting a proportion of women >70%. In addition, the samples tended to mostly include young adults, though studies often reported mean age rather than the median age.…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…Snowball sampling, in which research subjects recruit other subjects, was the most frequently used method to enroll general population study participants. The proportion of women in such samples ranged from 24.9% in Turkey 28 to 91.4% in China, 74 with nearly half of the study samples reporting a proportion of women >70%. In addition, the samples tended to mostly include young adults, though studies often reported mean age rather than the median age.…”
Section: Study Design and Sample Characteristicsmentioning
confidence: 98%
“…Another widely used instrument was the PTSD Checklist PCL-5, 27 which assesses PTSD symptoms experienced in the past month. The use of cutoff scores tended to be homogeneous, typically 31 28,29 or 33, 30,31 scores that have been previously validated in military veterans. 32 Some used symptom-criteria either alone 33,34 or in combination with a cutoff score.…”
Section: Ptsd Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of coronavirus disease 2019 (COVID‐19) and its numerous sequelae have led to a growing body of research addressing the mental health outcomes for exposure to the pandemic. Responding to Holmes et al ( 2020 ) call for research regarding the mental health effects of the COVID‐19 pandemic, many studies have found evidence for elevated levels of anxiety, depression, posttraumatic stress disorder symptoms, and distress in residents of China (e.g., Qiu et al, 2020 ), Italy (Forte et al, 2020 ), Spain (Gonzalez‐Sanguino et al, 2020 ), Germany (Bäuerle et al, 2020), India (Varshney et al, 2020 ), Egypt (El‐Zoghby et al, 2020 ), Turkey (Kira, Alpay, et al, 2021 ), Hong Kong (Choi et al, 2020 ), and the USA (Liu, Zhang, Wong, et al, 2020 ). These studies offer evidence for conceptualizing the experience of COVID‐19 as a potentially traumatic experience (e.g., Kira et al, 2020b ) with severe mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The current study added that while WTELS is directly associated with lower depression, anxiety, PTSD, and the novel COVID-19 traumatic stress syndrome, its positive effects on executive functions mediate its indirect effects. Recent studies found that COVID-19 traumatic stress is associated with increased executive function deficits (Kira, Alpay, Ayna, et al, 2021a;Kira, Alpay, Turkeli, et al, 2021b).…”
Section: Conclusion and Discussionmentioning
confidence: 99%